1997
DOI: 10.1542/peds.100.6.954
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function After Short-term Ibuprofen Use in Infants and Children

Abstract: Although renal failure in children has been reported after ibuprofen use, these data suggest that for short-term use the risk of less severe renal impairment, as reflected by blood urea nitrogen and creatinine levels, is small and not significantly greater than that after acetaminophen use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 11 publications
0
45
1
3
Order By: Relevance
“…A total of 385 (1.4%) children were hospitalised and in 112, plasma creatinine was measured and revealed normal levels [8]. Another study by the same authors concluded that ibuprofen had a good renal tolerance if given for a short period of time for antipyretic treatment [7]. However, it should be considered that the local synthesis of prostaglandins is less diminished by antipyretic doses of acetylsalicylic acid compared to NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 385 (1.4%) children were hospitalised and in 112, plasma creatinine was measured and revealed normal levels [8]. Another study by the same authors concluded that ibuprofen had a good renal tolerance if given for a short period of time for antipyretic treatment [7]. However, it should be considered that the local synthesis of prostaglandins is less diminished by antipyretic doses of acetylsalicylic acid compared to NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methods of the Boston University Fever Study have been described 4,5 and are only briefly summarized here. The study was a practitioner-based, double-blind clinical trial designed to assess the safety of ibuprofen suspension when used to treat fever in children.…”
Section: Methodsmentioning
confidence: 99%
“…61,63 However, it is not possible to determine the actual incidence of ibuprofen-related renal insufficiency after short-term use, because it has not been systematically investigated or reported. 64 Children who are at greatest risk of ibuprofen-related renal toxicity are those with dehydration, cardiovascular disease, preexisting renal disease, or the concomitant use of other nephrotoxic agents. 62 Another potential group at risk is infants younger than 6 months because of the possibility of differences in ibuprofen pharmacokinetics and developmental differences in renal function.…”
Section: Ibuprofenmentioning
confidence: 99%